Integrasi Gamifikasi dan Model Pembelajaran Problem Based Learning (PBL) pada Pembelajaran Kimia dalam Peningkatan Keterampilan Berpikir Kritis: Suatu Tinjauan Literatur - Sholihah, Khoirur Rohmaniatush; Djono (Universitas Sebelas Maret, 2025)
21st-century education requires students to master the 4C skills, which include critical thinking, collaboration, communication, and creativity. This study is based on the problem of low student analytical skills influenced by the dominance of teacher-centered learning, limited use of digital media, and the inconsistency of learning strategies with the demands of 21st-century competencies. This study aims to examine the use of gamification-based learning and problem-based learning in improving students' critical thinking skills. The research method used in this study is a literature review method by compiling various national and international publications published in the last five years collected through searches of academic databases (Scopus, Google Scholar, DOAJ, and Sinta). The results of the study indicate that the application of gamification and problem-based learning has provided consistent improvements in student motivation, engagement, and learning outcomes. Educational games have provided a learning environment that allows for independent exploration, strengthening reflective reasoning, and improving decision-making skills. However, the effectiveness of implementing this strategy is still influenced by the teacher's pedagogical competence, the availability of technological infrastructure, and the quality of alignment between game design and learning objectives. Based on the synthesis results, this study concludes that the integration of gamification and problem-based learning has strategic potential to support the transformation of learning toward a more adaptive and learner-oriented approach. These findings are expected to form the basis for developing innovative learning models that are relevant and effective in strengthening students' critical thinking skills.